What's so critical about it? An analysis of critique within different strands of critical gerontology. Issue 10 (25th October 2021) - Doheny, Shane; Jones, Ian Rees
Abstract: Shortly after emerging in the 1980s, critical gerontology became a recognised part of mainstream gerontology. Under the umbrella of 'critical gerontology' sits a number of orientations that draw attention to how ageing is socially located, while foregrounding the importance of values in ageing research. Nevertheless, as critical gerontology is not a clearly defined field or orientation, inconsistencies in the use of 'critique' among critical gerontologists has been fermenting internal tensions. In this paper we draw on recent debates on critique as a form of discourse that aims to criticise a deficient social order with the aim of helping to bring about a good society, to identify four discourses of critique. These include the discourses of immanent critique and of transcendent critique, critique that focuses on tensions between these two, and critique that builds on constructive combinations of immanence and transcendence. We add to these an extra level of depth by distinguishing how critical discourse is applied in each case. We use this framework to identify the discourses of critique deployed in variants of critical gerontology. Here, we distinguish political economic, lifecourse, humanistic and culturalist approaches within critical gerontology and assess how each of these applies a discourse of critique. We find that these gerontological perspectives draw on a variety of discourses of critique and make use of varying degrees of engagement with critical discourse. The paper concludes by discussing how critical gerontology may develop as a reflective forum commenting on and integrating insights offered by its own varieties of critique and connecting these with macro-social analyses.